Peripheral Immune System Adaptations and Motivation for Alcohol in Non‐Dependent Problem Drinkers. (1st February 2017) - Milivojevic, Verica; Ansell, Emily; Simpson, Christine; Siedlarz, Kristen M.; Sinha, Rajita; Fox, Helen C.
Abstract : Background: Increasing evidence suggests that levels of pro‐inflammatory and anti‐inflammatory cytokines are dysfunctional in alcohol dependence. Moreover, some initial findings demonstrate that these adaptations in peripheral inflammation may contribute to motivation for alcohol and problem drinking via possible direct effects or the indirect effects of stress responsivity. Importantly, the role of pro‐inflammatory and anti‐inflammatory cytokines in the progression from healthy to problem drinking is not well understood. The aim of this study was to assess whether alcohol‐related peripheral immune system changes affect stress and alcohol cue‐induced craving and anxiety and behavioral alcohol motivation and intake in the laboratory among problem drinkers compared with socially drinking controls. Methods: Twenty‐six problem drinkers and 38 moderate, social drinkers participated in a laboratory challenge procedure during which they were exposed to 3 personalized 5‐minute imagery conditions (stress [S], relaxing [R], and alcohol cue [C]), followed by the "alcohol taste test" (ATT) as a measure of implicit alcohol motivation and intake, presented across 3 consecutive days, 1 per day in a randomized and counterbalanced order. Measures of tumor necrosis factor‐alpha (TNF α ), interleukin‐6 (IL‐6), interleukin‐1 receptor antagonist (IL‐1ra), alcohol craving, and anxiety were assessed at baseline, immediately following imagery exposure and at discreet beer cue presentation in the ATT. Results: Compared with moderate drinkers, problem drinkers demonstrated tonic attenuation of IL‐6 and IL‐1ra. In problem drinkers, these changes also accompanied elevated levels of stress‐ and cue‐induced alcohol craving and anxiety and were predictive of provoked alcohol craving, behavioral alcohol motivation and intake, and severity of problem drinking. Conclusions: Current findings indicate that selective immunosuppression in problem drinkers may play a key role in motivation for alcohol intake. Abstract : This study assessed immune system changes in problem drinkers compared with socially drinking controls and whether these changes affect alcohol‐related behaviors. Problem drinkers compared with social drinkers demonstrated tonic attenuation of IL‐6 and IL‐1ra. These changes accompanied elevated levels of stress‐ and cue‐induced alcohol craving and anxiety and were predictive of provoked alcohol craving, behavioral alcohol motivation and intake, and severity of problem drinking. These findings indicate that immunosuppression in problem drinkers may play a key role in motivation for alcohol intake.